An unexpected case of ectopic pregnancy of the mesosalpinx - Siew, Jia Yun Shayna; Liu, Jia Yi; Goh, Siak Ming (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
1.3% of ectopic pregnancies occur in the abdominal cavity and these have 7.7 times higher mortality rates than tubal pregnancies. We presented a case who came at 5 weeks of amenorrhea with lower abdominal pain, vomiting, and vaginal bleeding. Ultrasound imaging showed a heterogenous vascular solid-cystic adnexal structure with hemoperitoneum. She underwent an emergency diagnostic laparoscopy. Intra-operatively, pregnancy was noted to be sited at the left proximal mesosalpinx. Ectopic pregnancy was removed through the ruptured point and the defect was stitched to restore anatomy and secure hemostasis. Risk factors, clinical presentation, and treatment of abdominal pregnancies are similar to that of any ectopic pregnancy. It is not unusual for diagnosis to be made only intra-operatively as in our case. The patient was offered a diagnostic laparoscopy due to a presumptive diagnosis of tubal pregnancy. As conception was early, completion resection was achieved. Abdominal pregnancy is uncommon and challenging to diagnose, therefore requires a high index of suspicion. Surgery is the mainstay treatment.